THE JATTI MIRIEK TRADITIONAL CLOTHING - Nashila, Japeri; Faridah, Sahari; Yakup, Mohd. Rafee (2019)
This study discusses the Jatti Miriek traditional clothing for men and women. The main purpose of this study is to analyze the pattern design, materials used, and the process of producing the Jatti Miriek traditional clothing. There are very restricted comprehensive studies and documentations on the traditional clothing that might lead to extinction of these valuable traditional details. The data in this study were collected through fieldwork involving interviews and visual observation. The findings of this study have shown that Jatti Miriek traditional clothing has its own uniqueness that should be documented for its influence on the design of Baju Melayu and Baju Kurung since the assimilation of Jatti Miriek ethnic. Therefore, this paper highlights the design of Jatti Miriek traditional clothing through discussions on visual comparison in order to generate empirical data on the details of the design. Furthermore, through this study it is expected to conserve the Jatti Miriek traditional clothing and serve as a guideline for future researchers.